2008
DOI: 10.1039/b800771c
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative addition of n-alkyl halides to diimine–dialkylplatinum(ii) complexes: a closer look at the kinetic behaviors

Abstract: The n-alkyl halides, RX, were oxidatively added to the platina(II)cyclopentane complexes [Pt[(CH2)4](NN)], in which NN = bpy (2,2'-bipyridyl) or phen (1,10-phenanthroline), to give the platinum(IV) complexes [PtRX[(CH2)4](NN)], R = Et and X = Br or I; R = nBu and X = I, 1-3. The same reactions with the analogous dimethyl complex [PtMe2(bpy)] gave the expected platinum(IV) complexes [PtRXMe2(bpy)], R = Et or nPr and X = Br or I; R = nBu and X = I, 4-8. Kinetics of the reactions in benzene and acetone was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…However, although the steric effect of the R group to some extent influences the reaction rate, it does not seem to be reasonable to attribute the order of reactivity to an increase in steric effects on going from R = CH 3 to R = Ph. The calculated results are in accord with experimental findings (in which the rate of reaction of 1a in acetone at 20°C with CH 3 CH 2 Br (k 2 = 1.43 × 10 −3 l mol −1 s −1 ) is nearly 10 4 times slower than that with PhCH 2 Br (k 2 = 11.61 l mol −1 s −1 )), [19] confirming that in this case the electronic nature of the R group is mainly responsible for the reactivity of bromide reagents and the influence due to bulkiness of the R groups is probably much less effective.…”
Section: Dft Studysupporting
confidence: 81%
See 2 more Smart Citations
“…However, although the steric effect of the R group to some extent influences the reaction rate, it does not seem to be reasonable to attribute the order of reactivity to an increase in steric effects on going from R = CH 3 to R = Ph. The calculated results are in accord with experimental findings (in which the rate of reaction of 1a in acetone at 20°C with CH 3 CH 2 Br (k 2 = 1.43 × 10 −3 l mol −1 s −1 ) is nearly 10 4 times slower than that with PhCH 2 Br (k 2 = 11.61 l mol −1 s −1 )), [19] confirming that in this case the electronic nature of the R group is mainly responsible for the reactivity of bromide reagents and the influence due to bulkiness of the R groups is probably much less effective.…”
Section: Dft Studysupporting
confidence: 81%
“…It is interesting to compare the behaviours of RCH 2 Br (R = CH 3 , Ph and PhCH 2 ) in their oxidative addition reactions with the organoplatinum(II) complex 1a with an emphasis on the differences between the effect of the R group of alkyl halides. Considering that second-order reactions for the reaction with CH 3 CH 2 Br and PhCH 2 Br are proposed to occur by the S N 2 mechanism, [18,19] we theoretically consider the S N 2 mechanism for oxidative addition of Pt(II) complex 1a with PhCH 2 CH 2 Br to conduct a systematic comparison based on the effect of R group on the rate of oxidative addition. The possible structures of the reactants, transition states, intermediates and products for the reaction of complex 1a with RCH 2 Br (R = CH 3 , Ph and PhCH 2 ) are shown in Scheme 2 along with their abbreviated names for ease of discussion.…”
Section: Dft Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Factors influencing the rate of the reactions and the kinetic parameters are also established. [1,2] Despite this, similar oxidative addition reactions involving dinuclear organoplatinum(II) complexes have not been investigated much. [4,5] These reactions could be important, as cooperative steric and/or electronic effects between the two adjacent metal centers may give rise to reaction pathways or products that are not possible in the kinetic data revealed that the reactions in nonpolar benzene or slightly polar CH 2 Cl 2 proceeded in two steps, each following a common S N 2 mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] This type of reaction plays a fundamental role in many industrially important catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%